Fifth Symphony by Ludwig van Beethoven According to Version by Ernst Theodor Amadeus Hoffmann: SAGLIETTI B. LA QUINTA SINFONIA DI BEETHOVEN RECENSITA DA E. T. A. HOFFMANN. NEL REGNO DELL’INFINITO. CON UN DIALOGO TRA L'AUTRICE E RICCARDO MUTI. ROMA: DONZELLI EDITORE. 115 P. - Saglietti, Benedetta (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
The purpose of the article is to characterize the research of its author entitled “Beethoven’s Fifth Symphony in the version of E. T. A. Hoffmann. In the kingdom of infinity” (Saglietti B. La quinta sinfonia di Beethoven recensita da E. T. A. Hoffmann. Nel regno dell’infinito), published in Turin in 2020. The monograph presents new scientific works on the creative heritage by L. van Beethoven; the events having taken place after the first performance of the composer's Fifth Symphony are considered; its musicological analysis, written by E. T. A. Hoffman in 1810, is characterized; its place and role in Italian musicology are determined. The Fifth Symphony was first performed in Vienna on December 22, 1808, this concert performance was as famous as it was unfortunate. The complexity of the piece, its insufficient rehearsal preparation, and the restraint of the audience caused a partial fiasco of the premiere. Beethoven was furious and foresaw negative reviews. Fortunately, he was wrong. Seven months later, the director of the largest German music newspaper, the “Allgemeine Musikalische Zeitung”, sent to Bamberg the edition of the symphony for piano four hands and an extensive review by E. T. A. Hoffmann, who was the first to recognize the Fifth Symphony as a masterpiece, thus determining its fate. It is his critical review that is considered one of the first reviews of music in the history, in the modern sense. But in Italy this original version was forgotten. Later, in “Fantasiestücke in Callot’s Manier” (1814 — first edition, 1819 — second), the review was published in an abridged form under the title “Beethoven's Instrumental Music” and translated into Italian several times. The monograph compares Hoffmann's review with its later, abridged version of the essay, and presents the author's methodology of the first Italian annotated edition; the circle of readers to whom Hoffmann appealed is outlined, it is emphasized that the Italian scholars have long accepted the essay as a review. The essay has been translated into French and English and has been published many times in German.